Formação continuada para professores de matemática: o erro como recurso pedagógico e seu papel no processo de avaliação - Rizzon, Bruna Moresco (My University, 2018)
Inserted in the research line "Fundamentals and Educational Strategies in Teaching Science and Mathematics", this dissertation presents the report of a study carried out with Mathematics teachers who work at Elementary Schools. The objective of the research was to analyze how (in which way) teachers understand the error in the context of the evaluation process, from the participation in a continuing training course on error analysis with the content of sequences and series. The main point was to answer the following question: what are the effects of the training course on teachers' awareness of the role of error in the evaluation process?. The theme of this research came as a possible continuity / extension of an earlier project, SECOPROF, in which a test about sequence and series was developed and applied to students of the Mathematics Degree and the Masters in Science and Mathematics Teaching of the University of Caxias do South (UCS). This test served as the basis for the elaboration of the continuing training course, which is the object and engine of this study, applied to teachers of the municipal education network of Caxias do Sul. For the planning, development and analysis of the course, a review of the literature on error and its usage as a strategy for learning, in sequence and series activities, and in the reflection on the evaluation process was carried out. The analyzes of the results and discussions were made according to David Tall's Three Worlds Theory, as well as Ball, Thames and Phelps' studies on the types of knowledge for teaching mathematics. It was also resorted to the thoughts of Cury and Borasi regarding the analysis of errors, and of Luckesi, in relation to the evaluation. Among the results of the research, the relevance attributed to the course by the participating teachers is highlighted, which, in self-assessment and evaluation instruments of the training, affirmed that the course promoted changes in the approach of student errors. This was also verified with various demonstrations of attention and concern that teachers had with their planning, taking advantage of mistakes of their students, identified in evaluation instruments and other recurrent ones, and preparing strategies to use errors as a possibility to do learning.
Inserida na linha de pesquisa “Fundamentos e Estratégias Educacionais no Ensino de Ciências e Matemática”, esta dissertação apresenta o relato de um estudo realizado com professores de Matemática que atuam no Ensino Fundamental. A pesquisa teve como objetivo analisar como (de que forma) os professores concebem o erro no contexto do processo de avaliação, a partir da participação em um curso de formação continuada sobre análise de erros em conteúdos de sequências e séries. Em linhas gerais buscou-se responder à seguinte questão: quais os efeitos do curso de formação na conscientização dos professores sobre o papel do erro no processo de avaliação?. O tema desta pesquisa surgiu como possível continuidade/extensão de um projeto anterior, o SECOPROF, no qual foi elaborado e aplicado um teste sobre sequências e séries a alunos da Licenciatura em Matemática e do Mestrado em Ensino de Ciências e Matemática da Universidade de Caxias do Sul (UCS). Tal teste serviu de base para a elaboração do curso de formação continuada, que é objeto e motor deste estudo, aplicado, por sua vez, a professores da rede municipal de ensino de Caxias do Sul. Para o planejamento, desenvolvimento e análise do curso, realizou-se uma revisão da literatura sobre o erro e sua utilização como estratégia para a aprendizagem, em atividades de sequências e séries e na reflexão sobre o processo de avaliação. As análises com vista aos resultados e discussões foram feitas de acordo com a Teoria dos Três Mundos, de David Tall, bem como com os estudos de Ball, Thames e Phelps sobre os tipos de conhecimento para o ensino da Matemática. Recorreu-se, ainda, aos pensamentos de Cury e Borasi no que diz respeito à análise de erros, e de Luckesi, em relação à avaliação. Dentre os resultados da pesquisa, destaca-se a relevância atribuída ao curso pelos professores participantes que, em instrumentos de autoavaliação e avaliação da formação realizada, afirmaram que o curso promoveu mudanças na abordagem dos erros dos alunos. Isso foi verificado, também, nas várias demonstrações de atenção e de preocupação que os professores tiveram com os seus planejamentos, aproveitando erros de seus estudantes, identificados em instrumentos de avaliação e outros recorrentes, e preparando estratégias de utilização dos erros como uma possibilidade de fazer avançar a aprendizagem.
Keywords: Professores - Formação; Matemática (Ensino fundamental); Aprendizagem; Avaliação educacional; Teachers, Training of; Mathematics (Elementary); Learning; Educational evaluation